Late Jurassic globetrotters compared: A closer look at large and giant theropod tracks of North Africa and Europe. (October 2019) - Belvedere, Matteo; Castanera, Diego; Meyer, Christian A.; Marty, Daniel; Mateus, Octavio; Silva, Bruno Camilo; Santos, Vanda F.; Cobos, Alberto
Abstract: Late Jurassic theropod tracks are very common both in North Africa and Europe. Two recently described ichnotaxa Megalosauripus transjuranicus and Jurabrontes curtedulensis from the Kimmeridgian of Switzerland show the coexistence of two apex predators in the same palaeoenvironment. Similar tracks can be found in tracksites from the Iberian Peninsula and from Morocco. Here, we further explore the similarities among the Swiss ichnotaxa and the other tracks from Germany (Kimmeridgian), Spain (Tithonian-Berriasian), Portugal (Oxfordian-Tithonian) and Morocco (Kimmeridgian) through novel three-dimensional data comparisons. Specimens were grouped in two morphotypes: 1) large and gracile (30 < Foot Length<50 cm) and 2) giant and robust (FL > 50 cm). The analyses show a great morphological overlap among these two morphotypes and the Swiss ichnotaxa ( Megalosauripus transjuranicus and Jurabrontes curtedulensis, respectively), even despite the differences in sedimentary environment and age. This suggests a widespread occurrence of similar ichnotaxa along the western margin of Tethys during the Late Jurassic. The new data support the hypothesis of a Gondwana-Laurasia faunal exchange during the Middle or early Late Jurassic, and the presence of migratory routes around the Tethys. Highlights: Digital ichnology allowed 3D comparison of tracks from different tracksites and palaeoenvironments. Analyses shows that there were two types of apex predators in those palaeoenvironments. Ichnotaxonomical reviews will profit of digital ichnology. Faunal exchanges between Gondwana and Laurasia are likely, but routes are not evident. Introduction.